Effect of Metronome Use on Chest Compression Rate in Cardiopulmonary Resuscitation (CPR) - Setianingsih, Setianingsih (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction : Cardio Pulmonary Resuscitation (CPR) is an intervention in the administration of chest compressions that aims to restore and maintain the function of vital organs in victims of cardiac arrest. The lack of quality of CPR in nursing students has an impact on the safety level of a person who experiences cardiac arrest. Therefore, nursing students need CPR skills training using metronome aids in determining the speed of chest compressions in accordance with American Heart Association (AHA) recommendations. The purpose of this study was to determine the effect of the use of metronome on the speed of chest compressions in CPR.Method: This research belongs to the quantitative type of design of Quasy Experiments (pseudo-experiments) pretest posttest without control groups. The sample used in this study was 25 students of the 6th semester nursing study program of Kendal Institute of Health Sciences. Sampling technique using purposive sampling.Result: The results of the study obtained that the average pre-intervention was 126 x / min and the average post-intervention was 117 x / min. The results of the hypothesis test using the Wilcoxon test obtained ap value of 0.036 (p <0.05) which means that there is an influence of the use of metronome on chest compression speed in CPR.Conclusions: Chest compression exercises using a metronome can be used to regulate the speed of chest compressions.